Contradictory Immune Response in Post Liver Transplantation Hepatitis B and C - Akinobu Takaki; Takahito Yagi; Kazuhide Yamamoto (International Journal of Inflammation)
Hepatitis B and C often progress to decompensated liver cirrhosis requiring orthotopic liver transplantation (OLT). After OLT, hepatitis B recurrence is clinically controlled with a combination of hepatitis B immunoglobulin (HBIG) and nucleos(t)ide analogues. Another approach is to induce self-producing anti-hepatitis B virus (HBV) antibodies using a HBV envelope antigen vaccine. Patients who had not been HBV carriers such as acutely infected liver failure or who received liver from HBV self-limited donor are good candidate. For chronic HBV carrier patients, a successful response can only be achieved in selected patients such as those treated with experimentally reduced immunosuppression protocols or received an anti-HBV adaptive memory carrying donor liver. Hepatitis C virus (HCV) reinfects transplanted livers at a rate of >90%. HCV reinfected patients show different severities of hepatitis, from mild and slowly progressing to severe and rapidly progressing, possibly resulting from different adaptive immune responses. More than half the patients require interferon treatment, although the success rate is low and carries risks for leukocytopenia and rejection. Managing the immune response has an important role in controlling recurrent hepatitis C. This study aimed to review the adaptive immune response in post-OLT hepatitis B and C.